Class, Demography, and Gay Politics in the West. (1st April 2020) - Cockshott, Paul
Abstract : We examine the economic position of gay couples and show that they are relatively advantaged compared to heterosexual ones, with this advantage being most marked for male same-sex couples. We argue that the issue of gay marriage has to be seen in the context of a general demographic crisis affecting Western capitalist countries. We look at the impact of this on profitability and growth.